2022
DOI: 10.3389/fphys.2022.1078763
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and athletes: Endurance sport and activity resilience study—CAESAR study

Abstract: Background: The COVID-19 pandemic and imposed restrictions influenced athletic societies, although current knowledge about mild COVID-19 consequences on cardiopulmonary and physiologic parameters remains inconclusive. This study aimed to assess the impact of mild COVID-19 inflection on cardiopulmonary exercise test (CPET) performance among endurance athletes (EA) with varied fitness level.Materials and Methods: 49 EA (nmale = 43, nfemale = 6, mean age = 39.94 ± 7.80 yr, height = 178.45 cm, weight = 76.62 kg; B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Due to the fact that 50% of the measurements in phase NZBC were affected by subject A's illness, the median across all data points (3.51 W/kg) probably did not reflect the actual performance of subject A (the MD of the two performances before disease: 3.65 W/kg). A study by Śliż et al [24] indicated that maximal heart rate and oxygen volume values could be less pronounced during cardiorespiratory graded tests, even long after COVID-19 infection. In subject A, this was found to be true with respect to oxygen volume when comparing the pre-(VO2 = 4.67 L/min) and post-COVID-19 (VO2 = 4.31 L/min) measurements in the NZBC phase.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that 50% of the measurements in phase NZBC were affected by subject A's illness, the median across all data points (3.51 W/kg) probably did not reflect the actual performance of subject A (the MD of the two performances before disease: 3.65 W/kg). A study by Śliż et al [24] indicated that maximal heart rate and oxygen volume values could be less pronounced during cardiorespiratory graded tests, even long after COVID-19 infection. In subject A, this was found to be true with respect to oxygen volume when comparing the pre-(VO2 = 4.67 L/min) and post-COVID-19 (VO2 = 4.31 L/min) measurements in the NZBC phase.…”
Section: Discussionmentioning
confidence: 99%
“…(5) EAs adopted different strategies of coping with stress, which was associated with the influence on lean body mass, (6) were analyzed in remaining CAESAR manuscripts [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that VO2peak is considerably lower in patients who have been hospitalized (29.2 ± 0.3 mL/kg/min) due to COVID-19 infection (and even worse in ICU patients with a mean VO2peak value of 25.5 mL/kg/min) compared to those who were non-hospitalized (33.7 ± 7.0 mL/kg/min) [6]; VO2peak in the latter group was comparable to that of our recreational athletes. Additionally, VO2peak has recently been shown to be a reasonable marker for demonstrating exercise limitations after mild COVID-19 infection in endurance athletes compared to CPET before the infec-tion (47.8 ± 7.8 mL/kg/min vs. 44.97 ± 7.00 mL/kg/min) [8]. However, the VO2peak findings from this study, which contained a similar sample size to that of our population (n = 49), must be interpreted with caution.…”
Section: The Benefit Of Cpet In Athletes With Pemmentioning
confidence: 99%
“…Although cardiorespiratory fitness expressed by VO2peak has been shown to be higher in non-hospitalized patients with COVID-19 infection as opposed to patients admitted to hospitals or even to the intensive care unit [6], hospitalization rates in athletes have been shown to be low [7]. However, a considerable decline in VO2peak has been demonstrated recently in endurance athletes following mild COVID-19 infection [8].…”
Section: Introductionmentioning
confidence: 99%